Quantitatively evaluate the impact of domestic aviation control measures on the spread of COVID-19 in China - Yu Wang; Ke Li; Ting Yuan; Yi Liu (Scientific Reports, 2022)
Abstract To quantitatively evaluate the impact of domestic aviation control measures on the spread of COVID-19 in China. The number of international flights from March to September 2019 simulated the number of flights from March to September 2020 without implementing aviation control measures. In addition, the proportion of asymptomatic persons and the delay in case reporting were adjusted to estimate the prevalence of each country during the same period and calculate the estimated imported cases. The estimated imported cases were assigned each day with weight, and the estimated daily reported cases were obtained based on the actual daily number of domestic cases in China. Effective Reproduction Number ( $$R_t$$ R t ) was calculated based on delayed distribution, Basic Reproductive Number ( $$R_0$$ R 0 ) distribution, and generation time distribution were reported in previous studies. Gaussian Process was used to estimate the effect of time-varying on $$R_t$$ R t , and the estimated $$R_t$$ R t was compared with the actual $$R_t$$ R t . The estimated imported cases increased significantly compared with the actual number of imported cases. The estimated imported cases were mainly concentrated in North America and Europe from March to April and gradually increased in many East Asian countries from May to September. The difference between predicted $$R_t$$ R t and actual $$R_t$$ R t was statistically significant. The estimated imported cases and the estimated $$R_t$$ R t have increased compared to the actual situation. This paper quantitatively proves that Chinese aviation control measures significantly suppress the COVID-19 epidemic, which is conducive to promoting and applying this measure.